Pengembangan Usaha Produksi Susu Kambing Dengan Penerapan Praktek Higiene Melalui Teat Dipping Dan Pasteurisasi Susu Pada Kelompok Ternak Di Desa Kolam Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Sihombing, Juli Mutiara; Silalahi, Parsaoran; Sinaga, Dearlina; Lumbantoruan, Mangonar; Purba, Aginta Immanuel; Harefa, Happy New Damai (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
The livestock business in Kampung Kolam village is dominated by dairy goats. One reason many dairy goat farmers raise goats in the area is to facilitate the sale of fresh goat milk products due to the proximity of Medan City and the abundance of land available to grow forage for dairy goats. The Community Service program was well-implemented and ran smoothly, meeting the established goals and plans. The questionnaire assessment given to participants during the Focus Group Discussion (FGD) before the presentation was 36.69%, and after the presentation, the understanding of hygiene practices increased to 93.33%. The community service team created and motivated all livestock group members to use teat dipping and pasteurization equipment according to procedures, ensuring proper hygiene practices, improving goat milk production in their businesses, and increasing their income and sales.